2015
DOI: 10.1158/1078-0432.ccr-15-0468
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Efficacy and Safety Assessment of an Antibody–Drug Conjugate Targeting the c-RET Proto-Oncogene for Breast Carcinoma

Abstract: Purpose: The RET proto-oncogene has been implicated in breast cancer, and the studies herein describe the preclinical and safety assessment of an anti-RET antibody-drug conjugate (ADC) being developed for the treatment of breast cancer.Experimental Design: RET protein expression was analyzed in breast tumor samples using tissue microarrays. The fully human anti-RET antibody (Y078) was conjugated to the DM1 and DM4 derivatives of the potent cytotoxic agent maytansine using thioether and disulfide linkers, respe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…The GFRA1 transcript levels correlates well with protein expression in a luminal A breast cancer tissues, suggesting that a high-throughput RNA-based diagnostic assay might suffice for patient selection instead of a IHC. RET, a receptor in GDNF-signaling is also known to be overexpressed in the breast cancer tissues (5,22), but we found it inferior to GFRA1 at both the mRNA and protein level, with only 6/29 (20%) samples expressing RET at 2þ/3þ in line with previous reports (20). Our IHC analysis further confirmed that RET is overexpressed with IHC score of 2þ/3þ only in 20% (6 of 29) patients, while 28% (8 of 29) patients showed IHC score 1þ and 52% (15 of 29) luminal A breast cancer patients showed no expression.…”
Section: Discussionmentioning
confidence: 99%
“…The GFRA1 transcript levels correlates well with protein expression in a luminal A breast cancer tissues, suggesting that a high-throughput RNA-based diagnostic assay might suffice for patient selection instead of a IHC. RET, a receptor in GDNF-signaling is also known to be overexpressed in the breast cancer tissues (5,22), but we found it inferior to GFRA1 at both the mRNA and protein level, with only 6/29 (20%) samples expressing RET at 2þ/3þ in line with previous reports (20). Our IHC analysis further confirmed that RET is overexpressed with IHC score of 2þ/3þ only in 20% (6 of 29) patients, while 28% (8 of 29) patients showed IHC score 1þ and 52% (15 of 29) luminal A breast cancer patients showed no expression.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, pheochromocytoma and paraganglioma would be expected to express high levels of RET since their tissues of origin intrinsically express high levels of RET. It has also been shown that more than half of all breast cancers express RET by immunohistochemistry (27). …”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first report where a headto-head comparison was made between two ADCs comprised of the same antibody but conjugated with payloads from different drug classes with different mechanisms of action: PBDs that form interstrand DNA cross-links and tubulysins that depolymerize microtubules. Others have reported comparing cleavable versus noncleavable drug linkers, but typically, these comparisons have included the same warhead class; for example, comparing conjugates with either cleavable mc-VC-PABC-MMAE or noncleavable mc-MMAF (45,46), or cleavable SPDB-DM4 versus noncleavable SMCC-DM1 (47,48). There have also been reports of comparing conjugates with auristatins and maytansinoids (49), but these are both inherently two classes of drugs with a similar mechanism of action, namely microtubule inhibition.…”
Section: Discussionmentioning
confidence: 99%